Mass Energy Absorption Coefficients Of Selected Biologically Equivalent Materials - Shakhreet, Bassam Zuhdi Othman (2001)
One of the most important gamma radiation quantities in respect of radiation dosimetry and health physics applications concerns is mass energy absorption. Direct measurements of the coefficient of mass-energy absorption, μen/ρ, are difficult and typically recourse is taken to theoretical computations. In this study we have determined μen/ρ using a simple and direct method based on paraxial sphere transmission using a proportional response gamma detector. The effects of nonparaxiality and of finite sample thickness have been accounted for, using extrapolation procedures. The deviation from nonproportionality and other corrections have been shown to be small.